Development of Sustainable Self-Compacting Concrete Using Slag Sand and Expanded Clay Aggregates - Bala, Usha Rani; Bhavani, R.; Jawahar, J. Guru (Salehan Institute of Higher Education, 2025)
The objective of this study is to develop a sustainable self-compacting concrete (SCC) by partially replacing natural aggregates with slag sand (SS) and lightweight expanded clay aggregate (ECA) in combination with a ternary binder system, thereby enhancing both performance and environmental sustainability. The methodology involved preparing thirty SCC mixes of M30 grade using 65% Ordinary Portland Cement, 25% fly ash, and 10% silica fume as binder, with slag sand replacing river sand at 20–100% and ECA replacing coarse aggregate at 20–100%. Fresh properties were evaluated through slump flow, T50, V-funnel, L-box, and U-box tests following EFNARC guidelines, while mechanical strength (compressive, split tensile, and flexural) was measured at 7, 28, and 90 days. Durability was assessed through sulphuric acid and magnesium sulphate exposure, and microstructural behavior was studied using FTIR and TGA. Results revealed that mixes with higher ECA content enhanced flowability, with A2B10 achieving superior workability (slump flow 694 mm, T50 2.9 s), while A2B6 (20% SS + 20% ECA) achieved optimum strength (45.21 MPa compressive) and durability retention under aggressive exposures. The novelty of this work lies in demonstrating the synergistic role of slag sand and ECA in producing SCC with enhanced performance, reduced natural aggregate usage, and improved sustainability compared to conventional SCC.